2014
DOI: 10.1208/s12249-014-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arginine on Pre-nucleus Stage of Interferon Beta-1b Aggregation

Abstract: Abstract. Understanding the mechanism of aggregation of a therapeutic protein would not only ease the manufacturing processing but could also lead to a more stable finished product. Aggregation of recombinant interferon (IFNβ-1b) was studied by heating, oxidizing, or seeding of unformulated monomeric solution. The formation of aggregates was monitored by dynamic light scattering (DLS) and UV spectroscopy. The autocatalytic monomer loss model was used to fit the data on aggregation rates. The influence of pre-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Proteins such as bevacizumab may follow the traditional Arrhenius relationship within a narrow temperature range between 25 1C and 50 1C; 116 however, most proteins do not behave this way for a wide range of temperatures. 117,118 Therefore, the rate of aggregation might be different at 25 1C than at 40 1C 70 due to the change in protein aggregate solubility, 119 various aggregation mechanisms, 120 conformational stability, 121 and the reversibility of protein aggregation 122 at different temperatures. Thus, prescribed storage temperatures for proteins based on accelerated stability data, 121 calculated using a modified Arrhenius equation 121 and the extended Lumry-Eyring (ELE) aggregation model should be followed.…”
Section: Temperaturementioning
confidence: 99%
“…Proteins such as bevacizumab may follow the traditional Arrhenius relationship within a narrow temperature range between 25 1C and 50 1C; 116 however, most proteins do not behave this way for a wide range of temperatures. 117,118 Therefore, the rate of aggregation might be different at 25 1C than at 40 1C 70 due to the change in protein aggregate solubility, 119 various aggregation mechanisms, 120 conformational stability, 121 and the reversibility of protein aggregation 122 at different temperatures. Thus, prescribed storage temperatures for proteins based on accelerated stability data, 121 calculated using a modified Arrhenius equation 121 and the extended Lumry-Eyring (ELE) aggregation model should be followed.…”
Section: Temperaturementioning
confidence: 99%
“…In other words, regardless of baseline cognitive capabilities, to some extent, all participants can exert top-down control over perception. For example, in two previous studies with healthy participants, all of them showed top-down attenuation of neural activity, regardless of their performance in other tasks ( Lopresti-Goodman et al, 2013 ; Fazeli et al, 2014 ).…”
Section: Simulation-adaptation Theory Of Hypnosis (Sath)mentioning
confidence: 88%
“…Single protein in the sample solution associates with another protein to form oligomer as the initial aggregation event and eventually lead to formation of higher multimers. The smallest aggregate is dimer, and the upper limit of size depends on protein properties and environmental conditions. , Usually, a larger molecular size can induce a low desorption/ionization efficiency and a decreased sensitivity in MALDI-TOF MS analysis. , Protein aggregation may be induced by undesirable solution conditions, the presence of a destabilizer/organic solvent, long-term storage, or under a single or several stress conditions, which may be observed in all stages of sample preparation and analysis. Several interventions, including chemical modification or mutation, lyophilization, and use of stabilizers, can be taken to inhibit protein aggregation. Site-specific mutations have proved to be effective in controlling protein aggregation, however, this approach is complex and may potentially affect protein integrity. Alternatively, protein stabilizers control the protein aggregation tendency mainly by reducing protein interactions and enhancing the conformational stability, such as amino acid derivatives, polysorbates, polyols, and sugars. It is also noted that protein stabilizers applied to one stress condition may be unsuitable to another due to potential differences in aggregation mechanisms.…”
Section: Introductionmentioning
confidence: 99%